Policing Talk: An investigation into the interaction of the officer and the suspect in the police interview. - Carter, Elisabeth Kate (International Journal of Speech, Language and the Law, 2009)
This thesis seeks to enhance knowledge of police interview interaction. Using a conversation analytic approach, this line-by-line analysis of the real-time interaction of suspects and officers empirically investigates previously unexplored and under explored areas of the police interview. This research uses the participants’ mutual understanding of and orientation to the context shown through their own talk to provide insights into particular phenomena, the wider contexts of the police interview and institutional interaction. It constitutes a substantial contribution to, and challenge of, traditional understandings of this aspect of criminal justice, which presents an original and innovative contribution to the field. This research explores 35 extracts from a corpus of 150 police interview tapes in which a police officer or officers interview a suspect arrested under suspicion of committing a criminal offence. The analytic chapters present the exploration of three interactional phenomena - the effect the tape, as a silent participant to the interaction, has on the structure of that interaction; the use and management of laughter by the officer and the suspect; and the in-depth examination of the elicitation of confessions from suspects by officers. Each analytic chapter explores the officers’ and suspects’ interactional construction of, maintenance of, and orientation to the police interview and each other through the presence and use of these phenomena. The first analytic chapter investigates the effect of the silent participants, that is, the potential future listeners of the tape, such as supervisory officers, a courtroom audience or members of a jury, who are represented in the interview through the physical presence of the tape recorder. Although research has explored the effect of the silent participant in other contexts, such as in newsroom interaction (Heritage and Greatbatch 1991) and courtroom interaction (Drew 1992), its effect in police interviews remains under explored. The findings of this research draws on its effect in other institutional contexts to establish how it may manifest in the police interview. It shows that officers produce redundant utterances and construct additional turns to accommodate the potential future audiences to the interaction. The findings also demonstrate the wider demands of the silent participant on the officers’ interaction and their need to maximise the admisibility of the interview. These demands are shown to override the local interactional needs of the suspect. Despite a wealth of research in other contexts, such as in ordinary conversation (Jefferson 1984, Brown and Levinson 1987, Billig 2005), comedy interactions (Rutter 1997) and doctor-patient interactions (West 1984, Haakana 2001), laughter remains unexplored in the context of the police interview. The second analytic chapter uses the structure of laughter established in both ordinary conversation and in other institutional contexts to frame the analysis of its use in the police interview. It reveals that laughter in the police interview is a tool which can be directed toward different objectives in accordance with the divergent positions, rights and obligations of the suspect and the officer. The research also reveals how laughter can be used by suspects to reinforce the veracity of their statements, and to facilitate a challenge of the officer. Conversely, laughter is also shown to be used by officers to challenge that very veracity of the suspect, and it is revealed that laughter can also be used by officers as a way in which they can circumvent the strictures of the PACE Act (1984) without sanction. The third analytic chapter explores the reality of the widely researched yet myth-laden phenomenon of the police interview confession through the line-by-line examination of its elicitation. It illustrates how knowledge claims and minimisation are used by officers in the successful elicitation of information that had previously been withheld by the suspect in the police interview. Knowledge claims (the officers use of knowledge external to the interview, such as deferring to witness or victim statements) were found to be used by officers as part of their challenge to the suspects’ versions of events and make it more difficult for the suspect to continue using a particular explanation. Minimisation, however, (such as an officer not directly referring to the crime, framing it as a misunderstanding, or minimising the potential consequences of the crime), was found to be used by officers to remove the disincentives of confessing and make it easier for the suspect to confess. Both of these techniques were found to be used by officers to create an interactional environment in which the suspect can confess. The research illustrates the modifications the use of phenomena undergo in their transposition from ordinary conversation and other institutional interaction to their use in police interviews. The manifestation of conversational and institutional orientations in the interaction of the police interview reveals much about the differences between the interactional, social and legal requirements of the contexts. It is through the analyses of the interactional phenomena that the constraints (seen in the officers’ adherence to the PACE Act 1984 overriding their orientation to the suspect) and the interests (such as the suspects’ use of laughter to project an image of innocence) of the individual participants are exposed. The reality of the police interview revealed in this research delivers the ability to examine the utterances of the participants, and on a deeper level, their motivations, orientations, and the requirements imposed upon them in the interview. The analyses offer distinctive and detailed insights into the reality of the myth and mystique of police interviews, findings which have the potential to inform and advance evidence-based police interview training and practice, and have the potential to signal a revisitation of the governance of the interactional conduct of police interviews in the efficacy of the PACE Act (1984).